Gastric content and perioperative pulmonary aspiration in patients with diabetes mellitus: a scoping review. (August 2021) - Xiao, Maggie Z.X.; Englesakis, Marina; Perlas, Anahi
Abstract: Background: Gastric emptying may be delayed in patients with diabetes mellitus (DM). However, the incidence of full stomach in fasting patients with DM and their risk of pulmonary aspiration under anaesthesia is not well understood. Methods: A scoping review was undertaken to map the literature on aspiration risk in DM. A search was conducted in seven bibliographic databases, including MEDLINE and Embase, for original articles that studied aspiration risk, gastric emptying, or gastric content and volume. Selection and characterisation were performed by two independent reviewers using a predefined protocol registered externally. Results: The search identified 5063 unique records, and 16 studies (totalling 775 patients with DM) were selected: nine studied gastric emptying and seven studied gastric content or volume. There were no studies reporting the incidence of aspiration in subjects with DM. All nine studies reported delayed emptying in patients with DM compared with healthy controls. Amongst the seven studies that compared gastric residual content/volume (GRV) in the perioperative period, five reported clinically negligible GRV in both patients with DM and controls, whereas two observed a higher incidence of 'full' stomach in patients with DM. Conclusions: The evidence concerning the aspiration risk for surgical patients with DM is based on a limited number of studies, mostly unblinded, reporting physiological data on gastric emptying and gastric volume as surrogate markers of aspiration risk. Data on fasting gastric content and volume in patients with DM are limited and contradictory; hence, the true risk of aspiration in fasting patients with DM is unknown.